THE ORGANIZATION OF JOINT ENTERPRISES IN THE REGIONS OF THE FERGHANA VALLEY AND THEIR ROLE IN THE ECONOMY OF THE COUNTRY - Oybek Turdimamatovich Nurmatov (Journals Park Publishing, 2022)
In the article, the establishment of joint ventures in the regions of Ferghana Valley and their role in the country’s economy is analyzed in detail with the help of primary sources and information from scientific literature.
Keywords: Ferghana Valley, Andizhan, Namangan, Ferghana, investment, joint venture, domestic and foreign policy.